1995
DOI: 10.1136/gut.37.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Acute diarrhoea induces rectal sensitivity in women but not men.

Abstract: Some patients with diarrhoea predominant irritable bowel syndrome have increased rectal sensitivity. It is uncertain, however, whether the diarrhoea is a consequence of the rectal sensitivity or if it is sensitising the rectum in some way. The aim of this study was to assess whether inducing diarrhoea in normal healthy volunteers can sensitise the rectum and therefore be a potential or partial cause of the sensitive rectum seen in some patients with diarrhoea predominant irritable bowel syndrome. The anorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…There is some support for this from a recent study which showed that experimental induction of acute diarrhoea by laxative ingestion could sensitise the rectum in normal volunteers 42. However, the finding of these physiological changes in the asymptomatic group (IBS−) questions their relation to the experience of IBS symptoms by our IBS+ patients.…”
Section: Discussionmentioning
confidence: 64%
“…There is some support for this from a recent study which showed that experimental induction of acute diarrhoea by laxative ingestion could sensitise the rectum in normal volunteers 42. However, the finding of these physiological changes in the asymptomatic group (IBS−) questions their relation to the experience of IBS symptoms by our IBS+ patients.…”
Section: Discussionmentioning
confidence: 64%
“…Sex differences have so far generally been neglected which is an unfortunate omission given that IBS is more frequently observed in females, 53 and that visceral hypersensitivity following episodes of acute diarrhoea can be induced in female but not in male patients. 54 The stimulus for further studies may come from recent data in patients with severe impairment of intestinal motor function which suggest that the inflammatory changes may involve neuromuscular tissue as well as the mucosa. [55][56][57] Preliminary data from patients with severe IBS symptoms indicated that an inflammatory infiltrate can sometimes be found in the myenteric plexus.…”
Section: Discussionmentioning
confidence: 99%
“…24 As an acute episode of diarrhoea induced by ingestion of an osmotic laxative is associated with an increase in rectal sensitivity in women (but not men), 25 and IBS patients seem to be more susceptible to sensitising events, [14][15][16][17][18] this may be the mechanism of the increased rectal sensitivity seen in IBS patients at menses. Alternatively, prostaglandins have been shown to induce afferent nerve sensitisation, 26 27 and as the gut of IBS patients may already be hypersensitive, prostaglandin release may be enough to trigger a further increase in this sensitivity.…”
Section: Discussionmentioning
confidence: 99%